MHD stagnation-point flow over a stretching/shrinking sheet in a micropolar fluid with a slip boundary - Siti Khuzaimah Soid,; Anuar Ishak,; Pop, Ioan (Penerbit Universiti Kebangsaan Malaysia, 2018)
The problem of stagnation point flow over a stretching/shrinking sheet immersed in a micropolar fluid is analyzed numerically. The governing partial differential equations are transformed into a system of ordinary (similarity) differential equation and are then solved numerically using the boundary value problem solver (bvp4c) in Matlab software. The effects of various parameters on the velocity and the angular velocity as well as the skin friction coefficient and the couple stress are shown in tables and graphs. The noticeable results are found that the micropolar and the slip parameters decrease the skin friction coefficient and the couple stress in the existence of magnetic field. Dual solutions appear for certain range of the shrinking strength. A stability analysis is performed to determine which one of the solutions is stable. Practical applications include polymer extrusion, where one deals with stretching of plastic sheets and in metallurgy that involves the cooling of continuous strips.